(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Community Service (PKM) carried out by Biology Education students at UIN Syarif Hidayatullah Jakarta from July 13 to August 29, 2024, in Kasepuhan Cirompang, Sobang District, Lebak Regency, is an effort to preserve local wisdom and improve the quality of education in the area. For 47 days, the student team has been active in various activities focused on literacy development and the Biodiversity School initiative. Kasepuhan Cirompang possesses unique cultural richness, reflected in various traditions such as asup leuweung, nibakeun, mapag, bubaran, and mipit. Using the action research method, this PKM aims to leverage the potential of local wisdom as a foundation for designing innovative and engaging literacy programs for children. This activity involved initial observation, program planning, implementation, evaluation, and follow-up. A total of 25 children and community members of Kasepuhan Cirompang actively participated in various activities. Implementation included the renovation of the Community Reading Park, the development of the Biodiversity School, implementation of Indonesian Language Time activities, as well as various other creative literacy initiatives. Furthermore, the literacy team also successfully created scientific boards, developed the Qiraati method, and compiled guidebooks on medicinal plants that are now used by the community. As a result, this activity not only increased reading interest but also fostered environmental awareness and empowered the community through the synergy of education and local wisdom.